Petrophilic, Fe(III) Reducing Exoelectrogen Citrobacter sp. KVM11, Isolated From Hydrocarbon Fed Microbial Electrochemical Remediation Systems - Venkidusamy, Krishnaveni; Hari, Ananda Rao; Megharaj, Mallavarapu (Frontiers in Microbiology, 2018)
Exoelectrogenic biofilms capable of extracellular electron transfer are important in advanced technologies such as those used in microbial electrochemical remediation systems (MERS) Few bacterial strains have been, nevertheless, obtained from MERS exoelectrogenic biofilms and characterized for bioremediation potential. Here we report the identification of one such bacterial strain, Citrobacter sp. KVM11, a petrophilic, iron reducing bacterial strain isolated from hydrocarbon fed MERS, producing anodic currents in microbial electrochemical systems. Fe(III) reduction of 90.01 ± 0.43% was observed during 5 weeks of incubation with Fe(III) supplemented liquid cultures. Biodegradation screening assays showed that the hydrocarbon degradation had been carried out by metabolically active cells accompanied by growth. The characteristic feature of diazo dye decolorization was used as a simple criterion for evaluating the electrochemical activity in the candidate microbe. The electrochemical activities of the strain KVM11 were characterized in a single chamber fuel cell and three electrode electrochemical cells. The inoculation of strain KVM11 amended with acetate and citrate as the sole carbon and energy sources has resulted in an increase in anodic currents (maximum current density) of 212 ± 3 and 359 ± mA/m2 with respective coulombic efficiencies of 19.5 and 34.9% in a single chamber fuel cells. Cyclic voltammetry studies showed that anaerobically grown cells of strain KVM11 are electrochemically active whereas aerobically grown cells lacked the electrochemical activity. Electrobioremediation potential of the strain KVM11 was investigated in hydrocarbonoclastic and dye detoxification conditions using MERS. About 89.60% of 400 mg l-1 azo dye was removed during the first 24 h of operation and it reached below detection limits by the end of the batch operation (60 h). Current generation and biodegradation capabilities of strain KVM11 were examined using an initial concentration of 800 mg l-1 of diesel range hydrocarbons (C9-C36) in MERS (maximum currentdensity 50.64 ± 7 mA/m2; power density 4.08 ± 2 mW/m2, 1000 ω, hydrocarbon removal 60.14 ± 0.7%). Such observations reveal the potential of electroactive biofilms in the simultaneous remediation of hydrocarbon contaminated environments with generation of energy.